The Use of Profiling to Target Services in State Welfare-to-Work Programs: An Example of Process and Implementation - Randall W. Eberts (W.E. Upjohn Institute for Employment Research, 1997)
The purpose of this paper is to provide preliminary information about the design of a pilot project to test the efficacy of profiling and referring welfare-to-work participants. Welfare reform requires welfare recipients, with few exceptions, to participate in work activities and ultimately become economically self-sufficient. Welfare recipients possess a wide variation in job readiness skills, ranging from those who are ready and able to work to those who face significant barriers to employment. The challenge of the local administrator of welfare-to-work programs is to target services to those who need them the most. Yet, most programs provide the same services to all participants, regardless of their past work history or skills. Profiling is a management tool that statistically identifies individuals as to the probability that they will obtain employment. The probability is derived from a statistical model using information commonly collected at enrollment interviews. The model estimates the relationship between an individual's propensity to find and hold a job and that person's attributes, work and welfare histories, and local labor market conditions. The paper describes the model and shows how it can be incorporated into existing welfare-to-work programs that emphasize work-related activities.
Keywords: J0; J6; 330; welfare-to-work; profiling; FDSS; Eberts; reemployment